Distal tubule bicarbonate reabsorption. - Vandorpe, David H. (University of Ottawa (Canada), 1990)
The purpose of this study was to elucidate certain aspects of the control of bicarbonate reabsorption in the surface distal tubule of rats made acidotic by ammonium chloride treatment. During acute metabolic acidosis, the effects of sodium delivery, water reabsorption, inhibition of carbonic anhydrase, and addition of the anion channel blocker SITS were determined. In addition, bicarbonate reabsorption was assessed during recovery from metabolic acidosis. Studies during the acute phase of acidosis: Sprague-Dawley rats were made acidotic by ammonium chloride gavage and then prepared for micropuncture. It was hypothesized that distal tubule bicarbonate transport might have components dependent on direct or indirect Na/H exchange, water reabsorption, carbonic anhydrase activity and chloride conductance. To test these hypotheses surface distal tubules were then microperfused in vivo at 8 nl/min with 4 different isoosmotic, bicarbonate containing solutions. These solutions were designed to (1) provide an index of the increased bicarbonate reabsorption evident in this model and assess the effect of the following on bicarbonate reabsorption: (2) sodium replacement with choline; (3) sodium substitution augmented by pharmacologic means (amiloride); (4) inhibition of carbonic anhydrase by acetazolamide. At 8 nl/min, collection of fluid from tubules perfused with all 4 solutions revealed significant bicarbonate reabsorption. Net distal tubule bicarbonate reabsorption was significantly increased in acidotic animals. Perfusion of tubules with sodium free solutions did not decrease this brisk reabsorptive flux, nor did perfusion of sodium free solutions which also contained amiloride. However, perfusion of tubules with the carbonic anhydrase inhibitor DIAMOX significantly decreased bicarbonate reabsorption. This is the first in vivo demonstration of such an effect in the distal tubule of the acidotic rat when bicarbonate load was held constant. The effect of sodium replacement at high perfusion rate was also studied, but again was not found to significantly alter bicarbonate reabsorption, although more bicarbonate was found to be reabsorbed at 25 nl/min than at 8 nl/min. Since some reports have suggested that a chloride conductance may play a role in acidification by proton pumps, the effects of perfusion with a chloride channel blocker was studied. Paired collections at 25 nl/min, with and without SITS, revealed a significant inhibitory effect of SITS. Studies during recovery from metabolic acidosis: Animals allowed to recover from the acidosis exhibited a rebound metabolic alkalosis. It was hypothesized that distal tubule bicarbonate reabsorption might contribute to this apparent overshoot of blood bicarbonate concentration. Tubules perfused 44 hours post gavage exhibited significant bicarbonate reabsorption at 8, 15, and 25 nl/min, despite the concurrent metabolic alkalosis. These are the first reported in vivo data of distal tubule bicarbonate reabsorption during rebound metabolic alkalosis. It is concluded that bicarbonate reabsorption in distal tubules of acidotic rats perfused in vivo at 8 nl/min was not affected by reduced sodium delivery, or water movement, but is partly dependent on carbonic anhydrase activity and may also be partly dependent on chloride permeability. In addition, bicarbonate reabsorption continues during the recovery phase, despite the existence of systemic metabolic alkalosis.
Keywords: Biology, Animal Physiology.